An Emerging Fault Related Fold (Mahad Anticline) and its Morphotectonic Interpretations in Northern Iraq - Hamdon, Alaa N.; Znad, Rabeea Khalaf (Iraqi Journal of Science, 2021)
In this study, morphotectonic analyses were prepared for an anticline existing to the north of Maqloub Anticline and extends toward north - south approximately, which is unfamiliar in relation to the major extension of the anticlines in the region. The study involves a structural interpretation of the anticline's origin and its relation with the faulting in the foreland zone in this area, specifically in foothill zone, because of the major fracture that is found adjacent and parallel to the axis of this anticline.The visual interpretation is the major tool used to determine the features of this anticline. Moreover, some facilitating remote sensing technologies, such as digital processing of satellite images and Digital Elevation Model data, were utilized to verify the shape of this geological feature. The origin of the fold was discussed through its relationship to the associated fault within the general tectonic framework and the surrounding areas. This study addresses the tectonic mechanism of the anticline as a fold-related fault mechanism.As a result, and through the compilation of the above interpretations, a final geological map was prepared for this anticline, along with a 3D model demonstrating its mechanism of folding. Proposed names were given to the anticline and the fault, which are Mahad Anticline and Mahad Fault , according to the name of their nearest town (Mahad Town).